1998
DOI: 10.1074/jbc.273.16.9527
|View full text |Cite
|
Sign up to set email alerts
|

Flavohemoglobin Expression and Function in Saccharomyces cerevisiae

Abstract: The yeast Saccharomyces cerevisiae contains a flavohemoglobin, encoded by the gene YHB1, whose function is unclear. Previous reports presented evidence that its maximal expression requires disruption of mitochondrial respiration and that it plays a role in the response to oxidative stress. We have studied the expression of YHB1 in respiratory deficient cells and in cells exposed to various compounds causing oxidative stress. Several different strains and approaches (spectroscopic detection of the oxygenated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 65 publications
1
18
2
Order By: Relevance
“…In any case, it now appears that the roles and functions of VHb are more complex than just the oxygen-transporting one initially believed. These hypothetical functions are different from the NO detoxification function proposed for flavohemoproteins from E. coli (22)(23)(24)(25)(26)(27). A recent study, however, indicates that NO detoxification may be a secondary but important function for VHb (28), whereas its primary function may be oxygen transfer, as supported by the data presented here.…”
Section: Construction Of Peg202::vgb and Pjg4-5::cyo Bo Ubiquinolcontrasting
confidence: 31%
“…In any case, it now appears that the roles and functions of VHb are more complex than just the oxygen-transporting one initially believed. These hypothetical functions are different from the NO detoxification function proposed for flavohemoproteins from E. coli (22)(23)(24)(25)(26)(27). A recent study, however, indicates that NO detoxification may be a secondary but important function for VHb (28), whereas its primary function may be oxygen transfer, as supported by the data presented here.…”
Section: Construction Of Peg202::vgb and Pjg4-5::cyo Bo Ubiquinolcontrasting
confidence: 31%
“…In contrast, transcription of the Saccharomyces cerevisiae flavohemoglobin, encoded by the YHB1 gene, is enhanced under oxygen-replete conditions via the hemedependent activation of the HAP1 and HAP2/3/4 transcription factors (10). Recently, it has been proposed that this flavohemoglobin might play a role in the oxidative stress response in yeast (11), but discrepancies in the results between different laboratories do not allow this conclusion (12); however, the results of phenotypic studies on YHB1-deleted or overexpressing strains suggest a complex relationship between Yhb1p function and cell defense against various stresses (12).…”
Section: Hemoglobins (Hbs)mentioning
confidence: 60%
“…YHB1 is not required for respiration, fermentation, or growth under any O 2 tension (20)(21)(22). It has been suggested that YHB1 may protect against oxidative stress (20), but this function has been questioned (21,22). Herein, we report that yeast YHB1 is required to metabolize NO and thereby protects against nitrosylation of cellular targets and inhibition of cell growth under both aerobic and anaerobic conditions.…”
mentioning
confidence: 84%
“…The expression of the yeast flavohemoglobin gene YHB1 is elevated under aerobic conditions (20,21), whereas E. coli hmp expression is not affected by O 2 (12). YHB1 is not required for respiration, fermentation, or growth under any O 2 tension (20)(21)(22). It has been suggested that YHB1 may protect against oxidative stress (20), but this function has been questioned (21,22).…”
mentioning
confidence: 99%